2020
DOI: 10.1037/dev0000800
|View full text |Cite
|
Sign up to set email alerts
|

An emotion coaching parenting intervention for families exposed to intimate partner violence.

Abstract: The current study describes a promising new emotion coaching (EC) parenting intervention for survivors of intimate partner violence (IPV) targeting emotion regulation (ER) and parent–child relationships. We discuss the development of an EC parenting intervention, outline its key elements, and use preliminary pilot data to illustrate how such a behavioral intervention can yield improvements in behavioral and physiological indices of ER (i.e., respiratory sinus arrhythmia [RSA]) and parent–child relationships an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…While Katz et al (2020) emotion coaching intervention was the only intervention we were able to find that specifically integrated components of DBT by name, many parent training interventions have shifted from focusing exclusively on modifying parents’ behavioral responses to children's problematic behaviors, to also incorporating emotion regulation and mindfulness components. While these are key components of DBT, there is a multitude of examples of parenting interventions integrating these components outside of a DBT framework.…”
Section: Dbt and Parenting Interventionsmentioning
confidence: 95%
See 1 more Smart Citation
“…While Katz et al (2020) emotion coaching intervention was the only intervention we were able to find that specifically integrated components of DBT by name, many parent training interventions have shifted from focusing exclusively on modifying parents’ behavioral responses to children's problematic behaviors, to also incorporating emotion regulation and mindfulness components. While these are key components of DBT, there is a multitude of examples of parenting interventions integrating these components outside of a DBT framework.…”
Section: Dbt and Parenting Interventionsmentioning
confidence: 95%
“…Parents may benefit from cues to be more mindful of their emotions and the benefits on checking in with themselves, before intervening with their child. This approach would focus on emotions while parenting and developing strategies to help reduce ineffective parenting practices related to strong emotions and impulsivity (Katz et al, 2020; Lengua et al, 2018).…”
Section: Recommendations For Treatment Providersmentioning
confidence: 99%
“…The combination of parents developing skills in responding to their children's emotional needs along with parents exploring their own family histories with emotions in the group, appears to have contributed to parents experiencing less stress and greater confidence in parenting. Katz and colleagues [21] also found working with parent emotion awareness and regulation was a vital part of their intervention that occurred prior to mothers learning emotion coaching skills with their children. Further, we have previously found that when parents had more emotional difficulties themselves, greater improvement in child behavior occurred when parents participated in TIK than for those parents who received a behavioral parenting intervention [15].…”
Section: Discussionmentioning
confidence: 99%
“…Their children also demonstrated significantly better memory and emotion knowledge relative to controls. Katz and colleagues' [21] twelve-week group parenting intervention for survivors of intimate partner violence addressed parent emotion awareness and regulation in early sessions before teaching emotion coaching skills in later sessions. In a pilot study with 50 mothers assigned to intervention or control, those receiving the intervention had improved parent emotion regulation on parent-report and physiological measures of respiratory sinus arrhythmia; improved observed and reported parenting and decreased parent-reported child depressive symptoms and decreased observed child negativity relative to controls who did not show these changes.…”
Section: Introductionmentioning
confidence: 99%
“…To directly measure child outcomes, studies have used assessment of emotion understanding, typically using Denham's (1986) puppet task, also referred to as the Affective Knowledge Test, the Emotion Skills Task, or the puppet interview (see Denham et al, 2015, for a review). In a study of an emotion coaching intervention on 75 mother-child dyads (child age 6-12) in households that had experienced intimate partner violence, Katz et al (2020) found increased baseline vagal tone in the intervention group children, taken to index increased ability of self-soothing in stressful situations (Porges, 1995). They also found improvement in mothers' emotion regulation abilities, mother and child mental health, parent-child relationship, and mothers' confidence in dealing with child behavior problems.…”
Section: Emotion Socialization Interventions and Child Self-regulationmentioning
confidence: 99%